Thermodynamic Analysis of a Rankine Cycle Powered Vapor Compression Ice Maker Using Solar Energy - Bing Hu; Xianbiao Bu; Weibin Ma (The Scientific World Journal, 2014)
To develop the organic Rankine-vapor compression ice maker driven by solar energy, a thermodynamic model was developed and the effects of generation temperature, condensation temperature, and working fluid types on the system performance were analyzed. The results show that the cooling power per square meter collector and ice production per square meter collector per day depend largely on generation temperature and condensation temperature and they increase firstly and then decrease with increasing generation temperature. For every working fluid there is an optimal generation temperature at which organic Rankine efficiency achieves the maximum value. The cooling power per square meter collector and ice production per square meter collector per day are, respectively, 126.44 W m−2 and 7.61 kg m−2 day−1 at the generation temperature of 140°C for working fluid of R245fa, which demonstrates the feasibility of organic Rankine cycle powered vapor compression ice maker.